CHANGES IN THE PROOXIDATIVE-ANTIOXIDANT SYSTEM IN SHR SERIES RATS WITH TREATMENT OF HYPOTENSIVE MEDICINES (RAMIPRIL AND CANDESARTANE) IN COMBINATION WITH CORVITIN - Marushchak, Aliona; Rohovyi, Yurii; Savchuk, Tetiana (The Ukrainian Scientific Medical Youth Journal, 2020)
Nowadays arterial hypertension (AH) is the most popular cardiovascular disease, which is the most common cause of disability in the population due to high risk of developing complications, such as heart failure, coronary artery disease, stroke. The nature of the morphological manifestations of hypertensive disease depends on the duration and severity, but hypertension triggers a cascade of pathological changes in the lung disease and is accompanied by disruption of the structure of organs that are the most sensitive to fluctuations of blood pressure (brain, heart, kidneys). Continuing the search for new drugs that not only lower blood pressure, but have polytropic effects. In the first place is cardioprotection, which is based on the principles of continuous monitoring of myocardial oxygenation and metabolism. Recently the attention of researchers attract bioflavonoids, such as corvitin, which showed antioxidant, prediabetics, anti-inflammatory properties. The question of influence corvitin in combination therapy with antihypertensive drugs in the treatment of hypertension has been insufficiently studied, that determines the relevance and purpose of our study. Materials and methods. The study was conducted spontaneously hypertensed of rats SHR series. Animals affected into 4 groups of observation. Experienced animal groups series SHR were administered ramipril at a dose of 5 mg / kg, candesartan 4 mg / kg and corvitin a dose of 50 mg/kg, and conducted combined therapy ramipril and corvitin, candesartan and corvitin. Drugs were administered for 7 days. State prooxidative-antioxidant system in the heart, liver, and kidney was estimated by the level of malondialdehyde (MDA) and has a diene conjugates (DC), the background activity of antioxidant enzymes: superoxiddismutase (SOD), glutathione peroxidase (TRP), of catalase (CT). The results of the study. Monotherapy with ramipril exacerbate the pathological process in the examined structures (kidney, heart, liver) and caused a decline in the level of antioxidant enzymes for the same level of malonic aldehyde and diene conjugates. Treatment with candesartan showed a more positive trend in reducing the level of products peroxidation and activation of superoxide dismutase, slightly increased the level of catalase remained unchanged and the activity of glutathione peroxidase. Combination therapy with carnitin significantly changed the indicators oxidative-antioxidant homeostasis in the direction of growth of activity of enzymes catalase and superoxide dismutase on the background of significant decrease of the products of barbituric acid. The most marked improvement was noted in the myocardium of the left ventricle and kidney in combination therapy with candesartan and corvitin. Conclusions. Application of corvitin in combination with antihypertensive drugs demonstrated protective effect. Increased level of blood pressure not only positive dynamics of combination therapy but also pleiotropy effect of corvitin.